Application of lnfiltration Trench as a Community Retention Facility in Seri Iskandar - Rahmat Sam, Mohd Farid (Universiti Teknologi PETRONAS, 2008)
This project exammes the application of infiltration trench as an extension and improvements from the Urban Stormwater Management Manual for Malaysia (MASMA) published by the Department of Irrigation and Drainage Malaysia. The infiltration trench is a structure which collects stormwater runoff and allows it to infiltrate into the soil strata. The trench provides temporary underground storage in the form of a storage chamber filled with an open-graded coarse stone aggregate. The Seri Iskandar soil which contains 78.28% sand, 2.48% silt and 1.06% clay was examined to see its suitability for the infiltration trench. The infiltration rate through the soil is 40.0 mmfhr which is higher than the requirement by MASMA of 13 mmfhr. The cation exchange capacity is equivalent to 1.63 meq of cations that can be absorbed by 1 OOg of dry soils of Seri Iskandar A model of infiltration trench conducted in laboratory using the Seri Iskandar soil was found to be able to remove 50% of COD, 72% of TSS, 31% of TP, 40% of ammonia-Nand 70% of zinc. Addition of lime to the soil improves the effectiveness of the soil in removing those pollutants and the addition of lime promoted Seri Iskandar soil to become porous, increases the soil pH and soil moisture.